4 William Waller Hening, The Statutes at Large: Being a Collection of all the Laws of Virginia 78 (1823) - (:unkn) unknown (My University, 1720)
Appropriated one thousand pounds to distribute "to each christian titheable [subject to taxation], one firelock, musket, one socket, bayonet fitted thereto, one cartouch box, eight pounds bullet, two pounds powder, until the whole one thousand pounds be laid out."
Keywords: MILITIAS